Lexicography of Énístēmi and the Eschatology of 1 Corinthians 7.25-26 and 2 Thessalonians 2.1-2 - Gathercole, Simon J. (Filología neotestamentaria, 2025)
This article analyses the meaning of the perfect tense of the Greek verb ἐνίστημι. This verb is controversial because of its usage by Paul and its relevance to early Christian eschatology. The first debated use comes in 1 Cor. 7.26, which has been interpreted as referring either to a present crisis or to an impending crisis, depending on the meaning of the perfect participle of ἐνίστημι. The second comes in 2 Thess. 2.2, according to which the Thessalonians are anxious that the day of the Lord either is here or is imminent, depending on the meaning of the perfect indicative of ἐνίστημι. This article aims to demonstrate beyond reasonable doubt that, where the perfect of ἐνίστημι has temporal connotations, it has a present not a future sense. A comprehensive analysis of the usage of the perfect of ἐνίστημι in the LXX, NT, the Apostolic Fathers, Philo, Josephus and Jewish Documentary Papyri provides no examples of the perfect of with a sense "be imminent" / "be impending". This is followed by a critical evaluation of various Greek lexica from the fifteenth century to the present. Evaluation of the parallels adduced over the centuries for the "impending" sense of the perfect of ἐνίστημι are shown to be inaccurate. All the linguistic evidence points to a consistent sense of the perfect of ἐνίστημι as meaning "be present" / "be here". There is also a legal usage of the perfect of èvíuŒnpu, but the formula refers to cases "in process" rather than "pending".